2004
DOI: 10.1177/009715580401500306
|View full text |Cite
|
Sign up to set email alerts
|

Digitizing Frenchness in 2001: On a ‘Historic’ Moment in the French Cinema

Abstract: Inexorably intertwined with American cinema, the digital French cinema has defined itself with and against its ever-present rival across the Atlantic. This article attempts to complicate what would be a predictable narrative of Americanization of French cinema, or the Gallicization of an American cinema by suggesting that at stake in this process is the historically rooted identity of Frenchness itself. It recalls that as the cinema has been one of the preeminent cultural activities of the French in terms of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Once he obtained it, however, he did not begin his magnum opus and struggle as a starving artist until he was able to bring it to fruition. Instead, he made a good living producing commercials and music videos (Austin, 2004;Dudley, 2004). In the 1990s, he gained a reputation that allowed him to work in feature film-though he did not cease his work in advertising-codirecting two highly successful products with Marc Caro.…”
Section: Amélie In Contextmentioning
confidence: 99%
“…Once he obtained it, however, he did not begin his magnum opus and struggle as a starving artist until he was able to bring it to fruition. Instead, he made a good living producing commercials and music videos (Austin, 2004;Dudley, 2004). In the 1990s, he gained a reputation that allowed him to work in feature film-though he did not cease his work in advertising-codirecting two highly successful products with Marc Caro.…”
Section: Amélie In Contextmentioning
confidence: 99%
“…The willingness of French cinema to "gallicize" Hollywood norms to enhance its competitiveness is perhaps exemplified by its turn to postproduction digitization, which, since its initial "explosion" in French cinema in 2001, has become increasingly prevalent. 5 The success of Luc Besson's English-language Léon is also particularly instructive: the product of a French auteur working within the Hollywood model, Léon suggested that the turn to a hybrid, postnational cinema was a new global market strategy that might depart from heritage film's presentation of an essentialized and commodified vision of national cultural identity. 6 Yet on the other hand, the discourse of exceptionalism also casts film as a key medium for the transmission of a cultural particularity under threat from globalizing and homogenizing forces.…”
Section: French Cinema As Global Competitormentioning
confidence: 99%